The seahills and seahills ecosystems in the nearshore of Thua Thien-Hue Province (Central Vietnam) - Bui , Van Vuong; Nguyen, Van Quan; Nguyen, Dac Ve; Nguyen, Duc The; Tran, Thi Thu Trang; Pham, Van Chien; Nguyen , Thi Kim Anh; Dang, Hoai Nhon; Nguyen, Thi Mai Luu; Hoang, Thi Chien; Le, Van Nam; Dinh, Hai Ngoc; et al. (Vietnam Journal of Marine Science and Technology, 2024)
At the seabed in the nearshore, Vietnam has sandbars, shoals, bedrock knobs, rock reefs, and other landforms with elevations a few to several tens of meters higher than the seabed, which is always under the lowest astronomical tide (chart datum) and material structure of diverse compositions such as sands, gravel, boulders, blocks, etc. They have determined and warned on the chart map for the safety of navigation and the navy. These areas are significant fishing grounds due to abundant fish, shrimp, and benthic organisms. However, until now, investigation, research, and knowledge regarding these landforms environment, biomes, and naturals have yet to be explored. This paper presents some initial results of natural features (morphology, genetic terrain, material compositions, and types), environmental features, ecological community features (diversity, major groups of organisms, marine fish resources), and their significance in marine biomes (distribution of organisms, ecological linkage, habitats of endemic species) of a sandbar, bedrock in the nearshore in Thuan An, Tu Hien - Chan May and Lang Co - Hai Van - Son Cha of Thua Thien-Hue province in the framework project of Thua Thien-Hue province and National Independent Project belongs to the National Program 562 with Code Number is ÐTÐLCN.78/22 and Vietnam Academy of Science and Technology Project with Code Number is ÐL0000.01/23–24. Based on these findings, the authors proposed naming this terrain “seahill” and the accompanying ecosystem “seahill ecosystems” in the nearshore of Vietnam while continuing to investigation, survey, and research.